2015
DOI: 10.1111/edt.12172
|View full text |Cite
|
Sign up to set email alerts
|

Are overweight/obese children at risk of traumatic dental injuries? A meta‐analysis of observational studies

Abstract: -Background/aim: Observational studies which investigated the association between overweight/obesity and traumatic dental injuries (TDI) reported contrasting results. Thus, this meta-analysis was designed to investigate such an association with the highest possible levels of internal and external validities. Material and methods: A comprehensive literature search was performed through PubMed, ISI Web of Science, Cochrane Library, Scopus, Google scholar to ensure generalizability. Eligible studies reported clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 65 publications
1
39
1
Order By: Relevance
“…The most remarkable result that emerged from this study is that overweight children were less likely to sustain TDIs. This is a rather surprising result since it contradicts a recent systematic review and meta‐analysis that has suggested a causative relationship between being overweight and TDIs . However, many epidemiological studies conducted in a comparable age group did not detect a significant association between TDIs and being overweight .…”
Section: Discussioncontrasting
confidence: 81%
“…The most remarkable result that emerged from this study is that overweight children were less likely to sustain TDIs. This is a rather surprising result since it contradicts a recent systematic review and meta‐analysis that has suggested a causative relationship between being overweight and TDIs . However, many epidemiological studies conducted in a comparable age group did not detect a significant association between TDIs and being overweight .…”
Section: Discussioncontrasting
confidence: 81%
“…Obesity and higher height for age have recently been found to be associated with TDI in preschoolers . Moreover, a recent systematic review of observational studies concluded that the risk of TDI is higher among overweight/obese schoolchildren . However, the quality of evidence in preschool children remains poor and these variables should continue to be investigated, especially in cohort studies .…”
Section: Factors Associated With Tdi In the Primary Dentitionmentioning
confidence: 99%
“…However, in the only study to identify a greater occurrence of TDI among taller children, both variables were collected in a cross‐sectional manner . A recent systematic review identified obesity as being associated with TDI, but nearly all studies analyzed had a cross‐sectional design and involved school children . Thus, few longitudinal studies have evaluated the effects of anthropometric variables on the occurrence of TDI, especially among preschool children.…”
Section: Introductionmentioning
confidence: 99%